1997
DOI: 10.1111/j.1471-0528.1997.tb12028.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical abortion or vacuum aspiration? Two year follow up of a patient preference trial

Abstract: Objective To describe and compare health outcomes two years after medical abortion or vacuum Design Women recruited to the original, partially randomised study were contacted for assessment using Setting Grampian region of Scotland, UK.Participants One hundred and forty women who had participated in a partially randomised study of first Intervention Vacuum aspiration or medical abortion using mifepristone and gemeprost.Main outcome measures Long-term general, reproductive and psychological health; acceptabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 21 publications
(29 reference statements)
4
43
1
1
Order By: Relevance
“…Findings of these studies are consistent with several others based on non-U.S. samples in suggesting that method of termination does not affect emotional adjustment or psychological experiences after the procedure among women given a choice of procedure (Ashok et al, 2005;Howie, Henshaw, Naji, Russell, & Templeton, 1997;Lowenstein et al, 2006).…”
Section: Prospective Studiessupporting
confidence: 80%
“…Findings of these studies are consistent with several others based on non-U.S. samples in suggesting that method of termination does not affect emotional adjustment or psychological experiences after the procedure among women given a choice of procedure (Ashok et al, 2005;Howie, Henshaw, Naji, Russell, & Templeton, 1997;Lowenstein et al, 2006).…”
Section: Prospective Studiessupporting
confidence: 80%
“…40 Depression is the main problem service providers have been concerned about. 21 Both the IES and HADS have been used in women after termination of pregnancy [21][22][23] and in our pilot study.…”
Section: Distress Anxiety and Depressionmentioning
confidence: 99%
“…This technique is being increasingly used in health technology assessment 32 and has been used previously for assessing strength of preference for abortion method. 23,33 Interviews will be conducted, using the payment card method, 34 in all women in the preference arm prior to the procedure where they will be asked to state their maximum 'willingness to pay' amount for the termination method they have chosen. Interviews will also be conducted on all women in both the randomised and preference arms at 2 weeks after the procedure when they will be asked to state their maximum 'willingness to pay' amount to receive their preferred option at a future date.…”
Section: Strength Of Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…21 Henshaw et al 14 performed a partially randomised preference trial of termination of pregnancy < 9 weeks and found no differences in depression, anxiety or low selfesteem 2 weeks after the procedure 22 nor, in a much smaller number, 2 years later. 23 Whether medical termination of pregnancy is associated with more adverse psychological consequences after 9 weeks' gestation is not known.…”
Section: Introductionmentioning
confidence: 99%